Functional ovarian tumors. - Ludmir, Abraham (2015)
Given the rarity of this type of neoplasms, little can be seen in the literature, that expresses enough experience in one hospital. There are a number of discrepancies regarding the classification, morphological details, histogenesis, diagnosis and treatment.